The Effectiveness of Acceptance and Commitment Therapy on Cognitive Emotion Regulation and Experiential Avoidance in Individuals with Leprosy in Tabriz - Mohaddes Ardabili, Fatemeh; Kazemi, Ameneh Sadat; Rasouli, Narges (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The present study aimed to determine the effectiveness of Acceptance and Commitment Therapy (ACT) on cognitive emotion regulation and experiential avoidance in individuals with leprosy in Tabriz.Methods and Materials: The research method was a quasi-experimental design with a pretest-posttest control group. The study population consisted of all individuals with leprosy in Tabriz in 2023. After a clinical interview and considering the inclusion and exclusion criteria, 32 participants were selected through convenience sampling and randomly assigned to experimental (n=16) and control (n=16) groups. Both groups were assessed using the Cognitive Emotion Regulation Questionnaire (Garnefski et al., 2002) and the Acceptance and Action Questionnaire (Bond et al., 2011). The experimental group received eight sessions of ACT over two months, with one 90-minute group therapy session per week. At the end of the treatment, both groups completed the cognitive emotion regulation and experiential avoidance questionnaires again. The data were analyzed using multivariate covariance analysis.Findings: The results of the data analysis showed a significant difference between the experimental and control groups in terms of cognitive emotion regulation and experiential avoidance in individuals with leprosy (P<0.01). After the intervention, the level of maladaptive emotion regulation and experiential avoidance in the experimental group significantly decreased compared to the pretest and control group, while adaptive emotion regulation in the experimental group significantly increased compared to the pretest and control group, leading to significant changes in cognitive emotion regulation and experiential avoidance.Conclusion: Therefore, the findings suggest that ACT affects cognitive emotion regulation and experiential avoidance in individuals with leprosy. The results of this study highlight some of the capabilities of this method in treating cognitive emotion regulation and experiential avoidance, demonstrating its potential as an effective therapy for individuals with leprosy.